2008
DOI: 10.1007/s12291-008-0081-8
|View full text |Cite
|
Sign up to set email alerts
|

Serum copper in Alzheimer’s disease and vascular dementia

Abstract: Alzheimer's disease is the most common form of dementia in the elderly

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
12
0

Year Published

2011
2011
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 29 publications
(13 citation statements)
references
References 23 publications
(22 reference statements)
1
12
0
Order By: Relevance
“…NINCDS-ADRDA criteria [44] and a Mini-Mental State Examination (MMSE) [45] score of 25 or less (range [16][17][18][19][20][21][22][23][24] were used for AD diagnosis.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…NINCDS-ADRDA criteria [44] and a Mini-Mental State Examination (MMSE) [45] score of 25 or less (range [16][17][18][19][20][21][22][23][24] were used for AD diagnosis.…”
Section: Methodsmentioning
confidence: 99%
“…Some studies of AD patients versus healthy controls reported an increase of circulating copper in AD [12][13][14][15][16][17][18]. Other studies have reported no variation [19][20][21][22][23][24][25][26].…”
Section: Introductionmentioning
confidence: 99%
“…Decreased concentration Unchanged concentration Cu Hippocampus, entorhinal cortex, frontal cortex, putamen (102,119) and senile plaques (121) Hippocampus, amygdala (99) , basal ganglia (116) and cortex (117) Hippocampus, cerebellum, cortex (98,99,118) , amygdala (99,118) and hippocampus (114) Fe Senile plaques (121) , amygdala, piriform cortex, olfactory system (109) , hippocampus/amygdala (99,124) , frontal cortex (102) , grey motor cortex (103,124) , temporal cortex (105) , hippocampus (106) , frontal/parietal/temporal lobe (107) , putamen/thalamus/globus pallidus/area occipitalis (108) and cortex (116) Basal ganglia (116) and hippocampus (114,115) Pituitary gland (125) CSF (61) levels of Cu in patients with AD or mild cognitive impairment (93) compared with healthy controls. In these studies, total Cu (78,80,94,139 -141) , ceruloplasmin (140,141) as well as 'free' Cu (ceruloplasmin non-bound Cu) (78,93,140,142,143) have been found at increased rates. The free Cu fraction correlated positively with CSF biomarkers of AD including Ab and hyperphosphorylated t (143) and inversely with MMSE (143) .…”
Section: Increased Concentrationmentioning
confidence: 96%
“…Non-ceruloplasmin bound copper (NCC) is slightly bound to peptides, albumin, amino acids and, due to its low molecular weight, is able to cross the brainblood barrier [32] so that the increase of plasma copper levels lowers cognitive function [5]. It has been found that high dietary intake of copper may be associated with accelerated cognitive decline [33] as well as the plasma copper levels in Alzheimer's patients is higher than that of healthy people [34] and copper-chelating agents slowed cognitive decline in Alzheimer's patients [35]. It is thought that a brain damage may occur due to the interaction of copper with copper with amyloid-β (Aβ) peptide which can cause a b amyloid (b-amyloid) conversion to rouge form, generating H 2 O 2 and impacts on cognition [5,32] but in this study there was no significant changes in copper levels in patients, as though there is no correlation between serum copper level and Alzheimer's patients in Iran [36].…”
Section: Discussionmentioning
confidence: 99%